Eliminating the Trade‐Off between the Throughput and Pattern Quality of Sub‐15 nm Directed Self‐Assembly via Warm Solvent Annealing. (19th November 2014) - Kim, Jong Min; Kim, YongJoo; Park, Woon Ik; Hur, Yoon Hyung; Jeong, Jae Won; Sim, Dong Min; Baek, Kwang Min; Lee, Jung Hye; Kim, Mi‐Jeong; Jung, Yeon Sik
<x xml:space="preserve">Abstract</x> The directed self‐assembly (DSA) of block copolymers (BCPs) has been suggested as a promising nanofabrication solution. However, further improvements of both the pattern quality and manufacturability remain as critical challenges. Although the use of BCPs with a high Flory‐Huggins interaction parameter (χ) has been suggested as a potential solution, this practical self‐assembly route has yet to be developed due to their extremely slow self‐assembly kinetics. In this study, it is reported that warm solvent annealing (WSA) in a controlled environment can markedly improve both the self‐assembly kinetics and pattern quality. A means of avoiding the undesirable trade‐off between the quality and formation throughput of the self‐assembled patterns, which is a dilemma which arises when using the conventional solvent vapor treatment, is suggested. As a demonstration, the formation of well‐defined 13‐nm‐wide self‐assembled patterns (3σ line edge roughness of ≈2.50 nm) in treatment times of 0.5 min (for 360‐nm‐wide templates) is shown. Self‐consistent field theory (SCFT) simulation results are provided to elucidate the mechanism of the pattern quality improvement realized by WSA.